Early Economic Thought and The Dynamics of Economic Thought - Asmi, Nur; Andriani, Rini; Siradjuddin, Siradjuddin (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2023)
This research aims to explore the history of the development and dynamics of economic thought, especially in the context of Islamic economics. The research was conducted using qualitative, descriptive and historiographic methods. Data were obtained through literature studies sourced from primary sources such as the Quran and Hadith, as well as secondary sources in the form of academic articles and previous research. This research identifies three main approaches that influence the development of Islamic economic thought, namely: (1) the legal approach, where classical scholars focused on legal aspects such as usury, zakat and the banking system; (2) the rational-critical approach where a number of researchers relied directly on the analysis of direct data on economic and social issues; (3) the dominant attitude of Muslim scholars towards Western economic science. The contributions of classical scholars include in-depth studies of fundamental concepts of Islamic economics such as riba, zakat, waqf, and interest-free financial systems. At the same time, modernist scholars criticized classical thinking and offered new explanations for contemporary economic problems. The mainstream approach has enriched empirical and theoretical research on Islamic economics. This study concludes that Islamic economic thought must remain grounded in its primary sources, the Quran and Hadith, while remaining open to new interpretations within the confines of Islamic teachings. Islamic economics is considered a dynamic system that continues to develop and adapt to changes in society, the needs of society, and the challenges of the times. This research is expected to provide a comprehensive understanding of the historical roots, theoretical foundations and prospects of Islamic economics in the future.